Bioactive Sr2+/Fe3+ co-substituted hydroxyapatite in cryogenically 3D printed porous scaffolds for bone tissue engineering. (2nd April 2021) - Yang, Liang; Ullah, Ismat; Yu, Keda; Zhang, Wancheng; Zhou, Jinge; Sun, Tingfang; Shi, Lei; Yao, Sheng; Chen, Kaifang; Zhang, Xianglin; Guo, Xiaodong
Abstract: Developing multi-doped bioceramics that possess biological multifunctionality is becoming increasingly attractive and promising for bone tissue engineering. In this view innovative Sr 2+ /Fe 3+ co-substituted nano-hydroxyapatite with gradient doping concentrations fixed at 10 mol% has been deliberately designed previously. Herein, to evaluate their therapeutic potentials for bone healing, novel gradient SrFeHA/PCL scaffolds are fabricated by extrusion cryogenic 3D printing technology with subsequent lyophilization. The obtained scaffolds exhibit desired 3D interconnected porous structure and rough microsurface, along with appreciable release of bioactive Sr 2+ /Fe 3+ from SrFeHA components. These favorable physicochemical properties render printed scaffolds realizing effective biological applications both in vitro and in vivo, particularly the moderate co-substituted Sr7.5Fe2.5HA and Sr5Fe5HA groups exhibit remarkably enhanced bioactivity that not only promotes the functions of MC3T3 osteoblasts and HUVECs directly, but also energetically manipulates favorable macrophages activation to concurrently facilitate osteogenesis/angiogenesis. Moreover, in vivo subcutaneous implantation and cranial defects repair outcomes further confirm their superior capacity to dictate immune reaction, implants vascularization and in situ bone regeneration, mainly dependent on the synergetic effects of released Sr 2+ /Fe 3+ . Accordingly, for the first time, present study highlights the great potential of Sr7.5Fe2.5HA and Sr5Fe5HA for ameliorating bone regeneration process by coupling of immunomodulation with enhanced angio- and osteogenesis and hence may provide a new promising alternative for future bone tissue engineering.